Flow and heat transfer in geothermal systems : basic equations for describing and modeling geothermal phenomena and technologies /: basic equations for describing and modeling geothermal phenomena and technologies. (2016) - Tóth, Anikó; Bobok, Elemér, 1938-
No abstract available